A Comprehensive Analysis using RStudio: Augmented Reality in Microbiology Mapping - Fidiastuti, Hasminar Rachman Fidiastuti (SEAQIS Journal of Science Education, 2025)
Augmented Reality (AR) is an emerging technology with significant potential across various domains, including microbiology. However, despite increasing interest, the research landscape at the intersection of AR and microbiology remains underexplored. This study conducts a bibliometric analysis to map the current state of research on AR in microbiology, identifying key trends, contributors, and thematic developments. Using RStudio and the bibliometric R-package, the researchers analysed publications indexed in the Scopus database from the past five years, employing performance analysis (e.g., publication growth, country productivity, and leading sources) and science mapping techniques such as co-word analysis and thematic mapping. The study focused on the keywords “augmented reality” and “microbiology” to identify relevant literature, resulting in 10 documents. The findings reveal a gradual increase in publications, especially in recent years, with the United States emerging as the leading contributor. Keyword co-occurrence analysis identified “augmented reality”, “microbiology”, and “human” as central themes. The thematic analysis highlighted key areas such as the design and evaluation of AR tools for microbiology education, their effects on student learning outcomes, and the challenges of integrating AR into instructional practices. These insights offer a foundation for advancing research and practical applications of AR in microbiology education. Future studies should continue to explore how AR can enhance learning experiences and outcomes in this field.